2013
DOI: 10.18546/ijdegl.05.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The development of the Global Citizenship Inventory for adolescents

Abstract: In this paper we report on the development of an inventory that measures global citizenship among adolescents. The methodology used consists of cognitive interviews for questionnaire design and explorative and confirmatory factor analyses among several datasets. The resulting Global Citizenship Inventory (GCI) includes a global citizenship behaviour index and three scales measuring principles underlying global citizenship: human equality, mutual dependency in the world, and the shared responsibility for solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…International school students who participated in our research felt they had much in common with people living in developing countries and that their behaviour could impact people in other countries. The Dutch students in our research disagreed on this point, a result that echoed the findings of Van Gent et al (2013) that Dutch young people feel powerless, indicating a lower degree of efficacy (Merryfield et al, 2008). Moreover, the Dutch school students in this study were negative about 'world citizenship' instead of 'national citizenship' (as indicated in statement 1), whereas international school students were slightly more positive, most likely because they felt that they belonged to two (or more) cultures or countries (Gerner et al, 1992;Van Dis, 2014).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…International school students who participated in our research felt they had much in common with people living in developing countries and that their behaviour could impact people in other countries. The Dutch students in our research disagreed on this point, a result that echoed the findings of Van Gent et al (2013) that Dutch young people feel powerless, indicating a lower degree of efficacy (Merryfield et al, 2008). Moreover, the Dutch school students in this study were negative about 'world citizenship' instead of 'national citizenship' (as indicated in statement 1), whereas international school students were slightly more positive, most likely because they felt that they belonged to two (or more) cultures or countries (Gerner et al, 1992;Van Dis, 2014).…”
Section: Discussionsupporting
confidence: 57%
“…As Van Gent et al (2013) show, there are differences of opinion on how young people in the Netherlands currently relate to the world. Research findings, for example, yield no clear answer on the question of whether young people today are more or less environmentally conscious than earlier generations.…”
Section: World-mindedness Of Young People In the Netherlandsmentioning
confidence: 99%